2009
DOI: 10.3354/meps07954
|View full text |Cite
|
Sign up to set email alerts
|

Fine-scale layer of hydromedusae is revealed by video plankton recorder (VPR) in a semi-enclosed bay in northern Norway

Abstract: High resolution images of zooplankton organisms were recorded in situ using a digital autonomous video plankton recorder (VPR) in a semi-enclosed bay in northern Norway. Data from vertical VPR profiles was used to estimate the depth distribution and abundance of zooplankton along a bay-wide grid. Images were recorded simultaneously with hydrographical data, and the spatial distribution of different organisms was related to several water column characteristics, such as chlorophyll a, density, and buoyancy frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…Graham et al 2001, Jacobsen & Norrbin 2009), the possible importance of density discontinuities and stratification per se must be considered. Both Arai (1992) and Frost et al (2010) concluded that hydromedusae behaviorally aggregate at salinity discontinuities.…”
Section: Vertical Distributions Of Ctenophores Medusae and Copepodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Graham et al 2001, Jacobsen & Norrbin 2009), the possible importance of density discontinuities and stratification per se must be considered. Both Arai (1992) and Frost et al (2010) concluded that hydromedusae behaviorally aggregate at salinity discontinuities.…”
Section: Vertical Distributions Of Ctenophores Medusae and Copepodsmentioning
confidence: 99%
“…Ctenophores, medusae, and copepods are known to accumulate at density discontinuities in the water column (Arai 1992, Graham et al 2001, Malej et al 2007, Jacobsen & Norrbin 2009, Frost et al 2010. Arai (1992) concluded that Sarsia tubulosa hydromedusae behaviorally aggregate at salinity discontinuities.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the existence of thin vertical layers has been rarely investigated, which is due to the low sampling efficiency of traditional net sampling for marine snow and the generally low ability of this method to resolve small-scale distribution patterns (Widder et al 1999, Alldredge et al 2002, Jacobsen & Norrbin 2009). Studies using optical and acoustical instruments have only recently started to quantitatively describe thin layers of marine snow at density gradients (Alldredge et al 2002, McManus et al 2003.…”
Section: Thin Layers Of Marine Snow and Mesozooplanktonmentioning
confidence: 99%
“…Recent advances in optical sampling methods, however, have allowed observations of plankton patches from microscale (<1 m) to small scale (1 to 10 m) (e.g. Davis et al 1992, Ashjian et al 2001, Jacobsen & Norrbin 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Such methods allow us to investigate marine multicellular plankton (e.g., copepods, pteropods, larvaceans and jellyfish) at ecologically meaningful scales (Benfield et al 1996, Remsen et al 2004, Jacobsen & Norrbin 2009). Optics-based surveys are also optimal for the observation of unicellular plankton possessing fragile siliceous skeletons, which are often fragmented and broken by sampling with a plankton net, with the result that their ecology (e.g.…”
Section: Introductionmentioning
confidence: 99%